Safety and efficacy of uninterrupted perioperative enteral feeding in pediatric burn patients. Issue 2 (March 2018) - Imeokparia, Folasade; Johnson, Morgan; Thakkar, Rajan K.; Giles, Sheila; Capello, Teresa; Fabia, Renata
Highlights: Early enteral nutrition has been shown to improve outcomes after burn injury. Uninterrupted perioperative feeding is proposed for pediatric burn patients. Uninterrupted perioperative feeds were feasible with no increase risk of aspiration. Patients with uninterrupted feeds effectively fulfilled metabolic demands and needs. Abstract: Introduction: Burn injuries are a significant cause of morbidity. Early enteral nutrition has been shown to improve outcomes, however enteral nutrition is often held for procedures receiving general anesthesia. Limited data is available on uninterrupted perioperative nutrition in pediatric burn patients. Methods: A single, American Burn Association verified burn center database was queried for patients ≤18 years of age with ≥15% total body surface area (TBSA) burn injuries who underwent surgeries with general anesthesia. Demographic and clinical details were analyzed comparing patients who were fed continuously and those with interrupted feeds. Results: Thirty-one patients met inclusion criteria. Eighteen had continuous feeds and thirteen had interrupted feeds. We found perioperative enteral feeds safe as there were no aspiration events in these patients. Patients with interrupted feeds lost an average of 119.1 kcal/kg and 1.4 days of estimated energy needs. This was a 125% fall below metabolic needs. This loss was more pronounced with multiple operations and for patients <30 kg. Patients with continuous feeds gained an average of 144.4 kcal/kg and 1.7 days of estimated energy needs. These patients surpassed metabolic needs by 173%. Again, this had the biggest impact in patients with multiple operations and those <30 kg. Conclusions: The metabolic demands of burn patients are above most critically ill patients. To meet these demands, we implemented uninterrupted perioperative feeding. There were no aspiration events. Continuous feeds were an effective means to achieve caloric demands and moderate catabolic injury. We demonstrated safety and efficacy of uninterrupted perioperative feeding of pediatric burn patients.